A light-curing lead-free and halogen-free solder paste and its preparation process
By adding specific components to lead-free and halogen-free solder paste and using photocuring technology, the problems of flux residue and insufficient soldering performance after soldering are solved, and the welding effect with high wetting, insulation resistance and low corrosion is achieved.
Patent Information
- Application Number
- CN202411586978.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-07
Smart Images

Figure BDA0005124519350000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solder paste, and in particular to a light-cured lead-free and halogen-free solder paste and a preparation process thereof. Background Art
[0002] As electronic products develop towards ultra-large-scale integration, digitization, and miniaturization, surface mount technology (SMT) has become the mainstream technology for electronic assembly. Solder paste is a new type of welding material that came into being with SMT. It is a paste-like mixture formed by mixing solder powder, flux, and other surfactants, thixotropic agents, etc. It is mainly used for welding electronic components such as resistors, capacitors, and ICs on the surface of PCBs in the SMT industry. As one of the key connecting materials in SMT, the quality of solder paste directly determines the reliability of surface mount devices. For example, poor-performance solder paste will cause electronic components to have defects such as tin beads, bridges, tombstones, and non-wetting after reflow soldering, which will seriously endanger the normal use of electronic products. It can be seen that it is particularly important to develop solder paste with excellent comprehensive performance and performance stability.
[0003] Traditional solder paste contains a large amount of lead, which is easy to produce a lot of smoke and dust. Long-term use will bring great harm to human living environment and safety. Most of the current lead-free solder paste contains halides such as fluorine, chlorine, bromine and iodine, which are difficult to recycle and are also easy to cause serious pollution to the environment. It is under this situation that lead-free and halogen-free solder paste came into being. However, after reflow soldering, the existing lead-free and halogen-free solder paste will have flux residue at the solder joint, and the residue generally appears in a soft and moist state, which is not conducive to the subsequent process. In addition, the lead-free and halogen-free solder paste on the market has more or less limited welding performance, the operator's frequency of scraping solder paste is high during use, the product has low wettability and low insulation resistance value after welding, a lot of residue, and high corrosiveness. Technical defects.
[0004] In order to solve the above problems, a Chinese invention patent with authorization announcement number CN115401358B discloses a light-curing solder paste and a preparation method thereof. The light-curing solder paste is made of raw materials including the following mass percentages: 8%-30% flux, and the rest is tin powder; each weight portion of the flux is made of raw materials including the following mass percentages: 20%-40% rosin, 0-5% thermoplastic resin, 10%-30% photoinitiator component, 3%-10% thickener, 0.1%-5% corrosion inhibitor, 5%-20% activator, and 40%-60% solvent. The light-curing solder paste of the application has the advantage of improving the curing effect of the solder paste after welding. However, the solder paste contains halogen components, so that its environmental performance needs to be further improved. In addition, the welding performance of the solder paste still needs to be further improved.
[0005] It can be seen that the art still needs a light-curing lead-free and halogen-free solder paste and a preparation process thereof with good welding performance, large wettability and insulation resistance values of the product after welding, good curing effect, less residue, and low corrosion. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a light-curing lead-free and halogen-free solder paste and its preparation process with good welding performance, large wettability and insulation resistance value of the product after welding, good curing effect, less residue and low corrosion.
[0007] To achieve the above object, the technical solution adopted by the present invention is: a light-curing lead-free and halogen-free solder paste, which is made of the following raw materials in percentage by weight: 10-25wt% halogen-free soldering flux, and the balance is lead-free solder powder; the lead-free solder powder is composed of the following components in percentage by weight: Ag 0.2-1wt%, Cu 0.08-0.5wt%, Ge 0.01-0.05wt%, Ni0.01-0.03wt%, Zn 0.05-0.1wt%, Sr The halogen-free soldering flux comprises the following components in parts by weight: 3-6 parts of rosin-based acrylamide monomer, 15-25 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 1-3 parts of N-acryloylmorpholine, 0.8-1.5 parts of 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate, 0.8-1.2 parts of amphoteric organic ion salt, 0.3-0.6 parts of adenosine, 0.1-0.3 parts of cellulose nanocrystals, 0.1-0.3 parts of diazolidinyl urea, 0.1-0.2 parts of photoinitiator, 3-5 parts of thixotropic agent, 5-8 parts of activator, 0.2-1 parts of surfactant, 0.1-0.3 parts of corrosion inhibitor and 25-35 parts of solvent.
[0008] Preferably, there is no special requirement for the source of the rosin-based acrylamide monomer. In one embodiment of the present invention, the rosin-based acrylamide monomer is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN105348422B.
[0009] Preferably, there is no special requirement for the source of the acrylate-terminated hyperbranched silicone-modified polyurethane. In one embodiment of the present invention, the acrylate-terminated hyperbranched silicone-modified polyurethane is prepared according to the method of Example 1 of Chinese invention patent with authorization announcement number CN111393608B.
[0010] Preferably, the amphoteric organic ion salt is at least one of hydroxypropane sulfonate pyridinium salt and 1-benzylpyridine-3-carboxylate.
[0011] Preferably, the cellulose nanocrystals have a length of 100-500 nm and a diameter of 20-100 nm, and are provided by Beijing Nanosyn Technology Co., Ltd.
[0012] Preferably, the photoinitiator is at least one of benzoin ethyl ether, benzoin dimethyl ether, benzoin isopropyl ether and benzoin butyl ether.
[0013] Preferably, the thixotropic agent is at least one of hydrogenated castor oil, castor oil, and ethylene bisstearamide.
[0014] Preferably, the active agent is at least one of decyltetradecanoic acid, 2-ethylimidazole, citric acid, salicylic acid, and terephthalic acid.
[0015] Preferably, the surfactant is at least one of ricinoleyl diethanolamine and polyethylene glycol 200.
[0016] Preferably, the corrosion inhibitor is at least one of benzotriazole, benzothiazole and benzimidazole.
[0017] Preferably, the solvent is at least one of diethylene glycol hexyl ether, diethylene glycol butyl ether, ethylene glycol hexyl ether and ethylene glycol butyl ether.
[0018] Another object of the present invention is to provide a process for preparing the light-curing lead-free and halogen-free solder paste, comprising the following steps:
[0019] Step S1, mixing the other components of the halogen-free soldering flux except the photoinitiator, thixotropic agent, activator, surfactant and corrosion inhibitor, heating to 120-130° C., stirring evenly in an oxygen atmosphere, then cooling to 65-80° C., continuing to add the thixotropic agent, activator, surfactant and corrosion inhibitor, stirring evenly, cooling to room temperature, adding the photoinitiator, stirring evenly to obtain the soldering flux;
[0020] Step S2, putting the soldering flux prepared in step S1 into a stirrer and stirring at a stirring speed of 20-100 rpm, then adding lead-free solder powder, stirring evenly to obtain a light-cured lead-free and halogen-free solder paste.
[0021] Preferably, the average particle size of the lead-free solder powder is 5-8 μm.
[0022] Due to the application of the above technical solution, the present invention has the following beneficial effects:
[0023] (1) The preparation process of the light-curing lead-free and halogen-free solder paste disclosed in the present invention is simple in preparation process, convenient in operation and control, high in preparation efficiency and finished product qualification rate, low in energy consumption, small in environmental impact, low in equipment dependence, suitable for continuous large-scale production, and has high value for promotion and application.
[0024] (2) The light-curing lead-free and halogen-free solder paste disclosed in the present invention comprises lead-free solder powder composed of the following components in weight percentage: Ag 0.2-1wt%, Cu 0.08-0.5wt%, Ge 0.01-0.05wt%, Ni 0.01-0.03wt%, Zn0.05-0.1wt%, Sr 0.01-0.03wt%, and the balance is Sn; through the reasonable selection of the component composition formula, the components can better interact with each other and improve their wettability, thereby ensuring good solderability and improving cost-effectiveness, safety and environmental protection.
[0025] (3) The light-curing lead-free and halogen-free solder paste disclosed in the present invention comprises the following components in parts by weight: 3-6 parts of rosin-based acrylamide monomer, 15-25 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 1-3 parts of N-acryloylmorpholine, 0.8-1.5 parts of 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate, 0.8-1.2 parts of amphoteric organic ion salt, 0.3-0.6 parts of adenosine, 0.1-0.3 parts of cellulose nanocrystals, 0.1-0.3 parts of diazolidinyl urea, 0.1-0.2 parts of photoinitiator, 3-5 parts of thixotropic agent, 5-8 parts of activator, 0.2-1 parts of surfactant, 0.1-0.3 parts of corrosion inhibitor, and 25-35 parts of solvent. By adding photoinitiator components to the flux, the flux can obtain a photocuring effect. Using ultraviolet light to irradiate the solder joints after reflow soldering can enhance the curing effect of the flux, reduce the flux residue, make the solder joint flux drier, improve the reliability of the solder joint, and provide a better foundation for the subsequent work process. Through the mutual coordination and joint action of the various components, the manufactured product has good welding performance, and after welding, the product has high wettability and insulation resistance, good curing effect, less residue, and low corrosion.
[0026] (4) The light-curing lead-free and halogen-free solder paste disclosed in the present invention has a reasonable composition, does not contain halogen or lead, has better environmental protection performance, and solves the influence of halogen on post-weld solderability. It has less post-weld residue and has good welding performance. After welding, the product has high wettability and insulation resistance, good curing effect and low corrosion. DETAILED DESCRIPTION
[0027] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.
[0028] Example 1
[0029] A light-curing lead-free and halogen-free solder paste is made of the following raw materials in percentage by weight: 10wt% halogen-free soldering flux and the balance is lead-free solder powder; the lead-free solder powder is composed of the following components in percentage by weight: 0.2wt% Ag, 0.08wt% Cu, 0.01wt% Ge, 0.01wt% Ni, 0.05wt% Zn, 0.06wt% Sr 0.01wt%, the balance is Sn; the halogen-free soldering flux comprises the following components in parts by weight: 3 parts of rosin-based acrylamide monomer, 15 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 1 part of N-acryloylmorpholine, 0.8 parts of 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate, 0.8 parts of amphoteric organic ion salt, 0.3 parts of adenosine, 0.1 parts of cellulose nanocrystals, 0.1 parts of diazolidinyl urea, 0.1 parts of photoinitiator, 3 parts of thixotropic agent, 5 parts of activator, 0.2 parts of surfactant, 0.1 parts of corrosion inhibitor, and 25 parts of solvent.
[0030] The rosin-based acrylamide monomer is prepared according to the method of Example 1 of the Chinese invention patent with authorization publication number CN105348422B; the acrylate-terminated hyperbranched silicone-modified polyurethane is prepared according to the method of Example 1 of the Chinese invention patent with authorization publication number CN111393608B.
[0031] The amphoteric organic ion salt is hydroxypropane sulfonic acid pyridinium salt; the cellulose nanocrystal has a length of 100-500nm and a diameter of 20-100nm, and is provided by Beijing Naxun Technology Co., Ltd.; the photoinitiator is benzoin ethyl ether; the thixotropic agent is hydrogenated castor oil; the active agent is decyl tetradecanoic acid; the surfactant is ricinoleyl diethanolamine; the corrosion inhibitor is benzotriazole; and the solvent is diethylene glycol hexyl ether.
[0032] A preparation process of the light-curing lead-free and halogen-free solder paste comprises the following steps:
[0033] Step S1, mixing the other components of the halogen-free soldering flux except the photoinitiator, thixotropic agent, activator, surfactant and corrosion inhibitor, heating to 120° C., stirring evenly in an oxygen atmosphere, then cooling to 65° C., continuing to add the thixotropic agent, activator, surfactant and corrosion inhibitor, stirring evenly, cooling to room temperature, adding the photoinitiator, stirring evenly to obtain the soldering flux;
[0034] Step S2, putting the soldering flux prepared in step S1 into a stirrer and stirring at a stirring speed of 20 rpm, then adding lead-free solder powder, stirring evenly to obtain a light-cured lead-free and halogen-free solder paste; the average particle size of the lead-free solder powder is 5 μm.
[0035] Example 2
[0036] A light-curing lead-free and halogen-free solder paste is made of the following raw materials in percentage by weight: 13wt% halogen-free soldering flux and the balance is lead-free solder powder; the lead-free solder powder is composed of the following components in percentage by weight: Ag 0.5wt%, Cu 0.15wt%, Ge 0.02wt%, Ni 0.015wt%, Zn 0.07wt%, Sr 0.015wt%, the balance is Sn; the halogen-free soldering flux comprises the following components in parts by weight: 4 parts of rosin-based acrylamide monomer, 17 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 1.5 parts of N-acryloylmorpholine, 1 part of 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate, 0.9 parts of amphoteric organic ion salt, 0.4 parts of adenosine, 0.15 parts of cellulose nanocrystals, 0.15 parts of diazolidinyl urea, 0.13 parts of photoinitiator, 3.5 parts of thixotropic agent, 6 parts of activator, 0.4 parts of surfactant, 0.15 parts of corrosion inhibitor, and 27 parts of solvent.
[0037] The rosin-based acrylamide monomer is prepared according to the method of Example 1 of the Chinese invention patent with authorization publication number CN105348422B; the acrylate-terminated hyperbranched silicone-modified polyurethane is prepared according to the method of Example 1 of the Chinese invention patent with authorization publication number CN111393608B.
[0038] The amphoteric organic ion salt is 1-benzylpyridine-3-carboxylate; the cellulose nanocrystal has a length of 100-500nm and a diameter of 20-100nm, and is provided by Beijing Naxun Technology Co., Ltd.; the photoinitiator is benzoin dimethyl ether; the thixotropic agent is castor oil; the active agent is 2-ethylimidazole; the surfactant is polyethylene glycol 200; the corrosion inhibitor is benzothiazole; and the solvent is diethylene glycol butyl ether.
[0039] A preparation process of the light-curing lead-free and halogen-free solder paste comprises the following steps:
[0040] Step S1, mixing the other components of the halogen-free soldering flux except the photoinitiator, thixotropic agent, activator, surfactant and corrosion inhibitor, heating to 123° C., stirring evenly in an oxygen atmosphere, then cooling to 70° C., continuing to add the thixotropic agent, activator, surfactant and corrosion inhibitor, stirring evenly, cooling to room temperature, adding the photoinitiator, stirring evenly to obtain the soldering flux;
[0041] Step S2, putting the soldering flux prepared in step S1 into a stirrer and stirring at a stirring speed of 40 rpm, then adding lead-free solder powder, stirring evenly to obtain a light-cured lead-free and halogen-free solder paste; the average particle size of the lead-free solder powder is 6 μm.
[0042] Example 3
[0043] A light-curing lead-free and halogen-free solder paste is made of the following raw materials in percentage by weight: 18wt% halogen-free soldering flux and the balance lead-free solder powder; the lead-free solder powder is composed of the following components in percentage by weight: 0.7wt% Ag, 0.3wt% Cu, 0.03wt% Ge, 0.02wt% Ni, 0.07wt% Zn, 0.06wt% Sr 0.02wt%, the balance is Sn; the halogen-free soldering flux comprises the following components in parts by weight: 4.5 parts of rosin-based acrylamide monomer, 20 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 2 parts of N-acryloylmorpholine, 1.2 parts of 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate, 1 part of amphoteric organic ion salt, 0.45 parts of adenosine, 0.2 parts of cellulose nanocrystals, 0.2 parts of diazolidinyl urea, 0.15 parts of photoinitiator, 4 parts of thixotropic agent, 6.5 parts of activator, 0.7 parts of surfactant, 0.2 parts of corrosion inhibitor, and 30 parts of solvent.
[0044] The rosin-based acrylamide monomer is prepared according to the method of Example 1 of the Chinese invention patent with authorization publication number CN105348422B; the acrylate-terminated hyperbranched silicone-modified polyurethane is prepared according to the method of Example 1 of the Chinese invention patent with authorization publication number CN111393608B.
[0045] The amphoteric organic ion salt is hydroxypropane sulfonic acid pyridinium salt; the cellulose nanocrystal has a length of 100-500nm and a diameter of 20-100nm, and is provided by Beijing Naxun Technology Co., Ltd.; the photoinitiator is benzoin isopropyl ether; the thixotropic agent is ethylene bisstearamide; the active agent is citric acid; the surfactant is ricinoleyl diethanolamine; the corrosion inhibitor is benzimidazole; and the solvent is ethylene glycol hexyl ether.
[0046] A preparation process of the light-curing lead-free and halogen-free solder paste comprises the following steps:
[0047] Step S1, mixing the other components of the halogen-free soldering flux except the photoinitiator, thixotropic agent, activator, surfactant and corrosion inhibitor, heating to 125° C., stirring evenly in an oxygen atmosphere, then cooling to 73° C., continuing to add the thixotropic agent, activator, surfactant and corrosion inhibitor, stirring evenly, cooling to room temperature, adding the photoinitiator, stirring evenly to obtain the soldering flux;
[0048] Step S2, adding the soldering flux prepared in step S1 into a stirrer and stirring at a stirring speed of 70 rpm, then adding lead-free solder powder, stirring evenly to obtain a light-cured lead-free and halogen-free solder paste; the average particle size of the lead-free solder powder is 6.5 μm.
[0049] Example 4
[0050] A light-curing lead-free and halogen-free solder paste is made of the following raw materials in percentage by weight: 23wt% halogen-free soldering flux and the balance is lead-free solder powder; the lead-free solder powder is composed of the following components in percentage by weight: Ag 0.9wt%, Cu 0.45wt%, Ge 0.04wt%, Ni 0.025wt%, Zn 0.09wt%, Sr 0.025wt%, the balance is Sn; the halogen-free soldering flux comprises the following components in parts by weight: 5.5 parts of rosin-based acrylamide monomer, 23 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 2.5 parts of N-acryloylmorpholine, 1.3 parts of 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate, 1.1 parts of amphoteric organic ion salt, 0.55 parts of adenosine, 0.25 parts of cellulose nanocrystals, 0.25 parts of diazolidinyl urea, 0.18 parts of photoinitiator, 4.5 parts of thixotropic agent, 7.5 parts of activator, 0.9 parts of surfactant, 0.25 parts of corrosion inhibitor, and 33 parts of solvent.
[0051] The rosin-based acrylamide monomer is prepared according to the method of Example 1 of the Chinese invention patent with authorization publication number CN105348422B; the acrylate-terminated hyperbranched silicone-modified polyurethane is prepared according to the method of Example 1 of the Chinese invention patent with authorization publication number CN111393608B.
[0052] The amphoteric organic ion salt is a mixture of hydroxypropane sulfonic acid pyridinium salt and 1-benzylpyridine-3-carboxylate in a mass ratio of 1:2; the cellulose nanocrystal has a length of 100-500nm and a diameter of 20-100nm, and is provided by Beijing Naxun Technology Co., Ltd.; the photoinitiator is a mixture of benzoin ethyl ether, benzoin dimethyl ether, benzoin isopropyl ether, and benzoin butyl ether in a mass ratio of 1:2:2:1; the thixotropic agent is hydrogenated castor oil, castor oil, and ethylene bisstearamide in a mass ratio of 1:3: 2; the active agent is a mixture of decyl tetradecanoic acid, 2-ethylimidazole, citric acid, salicylic acid, and terephthalic acid in a mass ratio of 1:1:2:1:2; the surfactant is a mixture of ricinoleyl diethanolamine and polyethylene glycol 200 in a mass ratio of 3:5; the corrosion inhibitor is a mixture of benzotriazole, benzothiazole, and benzimidazole in a mass ratio of 1:2:3; the solvent is a mixture of diethylene glycol hexyl ether, diethylene glycol butyl ether, ethylene glycol hexyl ether, and ethylene glycol butyl ether in a mass ratio of 1:1:3:2.
[0053] A preparation process of the light-curing lead-free and halogen-free solder paste comprises the following steps:
[0054] Step S1, mixing the other components of the halogen-free soldering flux except the photoinitiator, thixotropic agent, activator, surfactant and corrosion inhibitor, heating to 128° C., stirring evenly in an oxygen atmosphere, then cooling to 78° C., continuing to add the thixotropic agent, activator, surfactant and corrosion inhibitor, stirring evenly, cooling to room temperature, adding the photoinitiator, stirring evenly to obtain the soldering flux;
[0055] Step S2, adding the soldering flux prepared in step S1 into a stirrer and stirring at a stirring speed of 90 rpm, then adding lead-free solder powder, stirring evenly to obtain a light-cured lead-free and halogen-free solder paste; the average particle size of the lead-free solder powder is 7.5 μm.
[0056] Example 5
[0057] A light-curing lead-free and halogen-free solder paste is made of the following raw materials in percentage by weight: 25wt% halogen-free soldering flux and the balance is lead-free solder powder; the lead-free solder powder is composed of the following components in percentage by weight: 1wt% Ag, 0.5wt% Cu, 0.05wt% Ge, 0.03wt% Ni, 0.1wt% Zn, 0.1wt% Sr 0.03wt%, the balance is Sn; the halogen-free soldering flux comprises the following components in parts by weight: 6 parts of rosin-based acrylamide monomer, 25 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 3 parts of N-acryloylmorpholine, 1.5 parts of 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methacrylate, 1.2 parts of amphoteric organic ion salt, 0.6 parts of adenosine, 0.3 parts of cellulose nanocrystals, 0.3 parts of diazolidinyl urea, 0.2 parts of photoinitiator, 5 parts of thixotropic agent, 8 parts of activator, 1 part of surfactant, 0.3 parts of corrosion inhibitor, and 35 parts of solvent.
[0058] The rosin-based acrylamide monomer is prepared according to the method of Example 1 of the Chinese invention patent with authorization publication number CN105348422B; the acrylate-terminated hyperbranched silicone-modified polyurethane is prepared according to the method of Example 1 of the Chinese invention patent with authorization publication number CN111393608B.
[0059] The amphoteric organic ion salt is hydroxypropane sulfonate pyridinium salt; the cellulose nanocrystals have a length of 100-500nm and a diameter of 20-100nm, and are provided by Beijing Naxun Technology Co., Ltd.; the photoinitiator is benzoin butyl ether; the thixotropic agent is hydrogenated castor oil; the active agent is salicylic acid; the surfactant is ricinoleyl diethanolamine; the corrosion inhibitor is benzimidazole; and the solvent is diethylene glycol butyl ether.
[0060] A preparation process of the light-curing lead-free and halogen-free solder paste comprises the following steps:
[0061] Step S1, mixing the other components of the halogen-free soldering flux except the photoinitiator, thixotropic agent, activator, surfactant and corrosion inhibitor, heating to 130° C., stirring evenly in an oxygen atmosphere, then cooling to 80° C., continuing to add the thixotropic agent, activator, surfactant and corrosion inhibitor, stirring evenly, cooling to room temperature, adding the photoinitiator, stirring evenly to obtain the soldering flux;
[0062] Step S2, adding the soldering flux prepared in step S1 into a stirrer and stirring at a stirring speed of 100 rpm, then adding lead-free solder powder, stirring evenly to obtain a light-cured lead-free and halogen-free solder paste; the average particle size of the lead-free solder powder is 8 μm.
[0063] Comparative Example 1
[0064] A light-curing lead-free and halogen-free solder paste and a preparation process thereof are substantially the same as those in Example 1, except that Ge, amphoteric organic ion salt and adenosine are not added.
[0065] Comparative Example 2
[0066] A light-curing lead-free and halogen-free solder paste and a preparation process thereof are substantially the same as those in Example 1, except that Sr, cellulose nanocrystals and diazolidinyl urea are not added.
[0067] In order to further illustrate the beneficial technical effects of the photocurable lead-free and halogen-free solder paste involved in each embodiment of the present invention, relevant performance tests were carried out on the photocurable lead-free and halogen-free solder paste involved in Examples 1-5 and Comparative Examples 1-2. The test results are shown in Table 1. The test method is as follows: refer to SJT 11186-2019 and SJ / T 11389-2019, and after reflow, use ultraviolet light with a wavelength of 365nm for 3 minutes to test wettability, surface insulation resistance, and copper mirror corrosion respectively. The viscosity of the solder paste residue is evaluated as follows: if the talcum powder can be easily brushed off with a soft brush, the solder paste residue has no viscosity; if the talcum powder cannot or is difficult to remove, the solder paste residue has viscosity.
[0068] Table 1
[0069]
[0070] As can be seen from Table 1, the photocurable lead-free and halogen-free solder paste involved in the embodiment of the present invention has better wettability, higher surface insulation resistance, lower corrosiveness, and no viscosity of the solder paste residue compared with the comparative example product. The addition of Ge, amphoteric organic ion salt, adenosine, Sr, cellulose nanocrystals and diazolidinyl urea is beneficial to improving the above properties.
[0071] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A light-curing lead-free and halogen-free solder paste, characterized in that: The invention is prepared from the following raw materials in percentage by weight: 10-25wt% halogen-free soldering flux, and the balance is lead-free solder powder; the lead-free solder powder is composed of the following components in percentage by weight: 0.2-1wt% Ag, 0.08-0.5wt% Cu, 0.01-0.05wt% Al, 0.01-0.03wt% Ni, 0.05-0.1wt% Zn, 0.01-0.03wt% Sr, and the balance is Sn; the halogen-free soldering flux comprises the following components in parts by weight: 3-6 parts of rosin-based acrylamide monomer, 15-25 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 1-3 parts of N-acryloylmorpholine, 0.8-1.5 parts of 2-[3-(2H-benzotriazole-2-yl)-4-hydroxyphenyl]ethyl 2-methylacrylate, 0.8-1.2 parts of amphoteric organic ion salt, and 0.3-0 .6 parts, cellulose nanocrystals 0.1-0.3 parts, diazolidinyl urea 0.1-0.3 parts, photoinitiator 0.1-0.2 parts, thixotropic agent 3-5 parts, active agent 5-8 parts, surfactant 0.2-1 parts, corrosion inhibitor 0.1-0.3 parts, solvent 25-35 parts; the amphoteric organic ion salt is at least one of hydroxypropane sulfonate pyridinium salt and 1-benzylpyridine-3-carboxylate; the photoinitiator is at least one of benzoin ethyl ether, benzoin dimethyl ether, benzoin isopropyl ether and benzoin butyl ether.
2. The light-curing lead-free and halogen-free solder paste according to claim 1, characterized in that: The length of the cellulose nanocrystal is 100-500nm and the diameter is 20-100nm.
3. The light-curing lead-free and halogen-free solder paste according to claim 1, characterized in that: The thixotropic agent is at least one of hydrogenated castor oil, castor oil, and ethylene bisstearamide; the activating agent is at least one of decyl tetradecanoic acid, 2-ethylimidazole, citric acid, salicylic acid, and terephthalic acid.
4. The light-curing lead-free and halogen-free solder paste according to claim 1, characterized in that: The surfactant is at least one of ricinoleyl diethanolamine and polyethylene glycol 200.
5. The light-curable lead-free and halogen-free solder paste according to claim 1, characterized in that: The corrosion inhibitor is at least one of benzotriazole, benzothiazole and benzimidazole.
6. The light-curable lead-free and halogen-free solder paste according to claim 1, characterized in that: The solvent is at least one of diethylene glycol hexyl ether, diethylene glycol butyl ether, ethylene glycol hexyl ether and ethylene glycol butyl ether.
7. A process for preparing the light-curable lead-free and halogen-free solder paste according to any one of claims 1 to 6, characterized in that: The steps include: Step S1, mixing the other components of the halogen-free soldering flux except the photoinitiator, thixotropic agent, activator, surfactant and corrosion inhibitor, heating to 120-130° C., stirring evenly in an oxygen atmosphere, then cooling to 65-80° C., continuing to add the thixotropic agent, activator, surfactant and corrosion inhibitor, stirring evenly, cooling to room temperature, adding the photoinitiator, stirring evenly to obtain the soldering flux; Step S2, putting the soldering flux prepared in step S1 into a stirrer and stirring at a stirring speed of 20-100 rpm, then adding lead-free solder powder, stirring evenly to obtain a light-cured lead-free and halogen-free solder paste.
8. The process for preparing the light-curing lead-free and halogen-free solder paste according to claim 7, characterized in that: The average particle size of the lead-free solder powder is 5-8 μm.
Citation Information
Patent Citations
A kind of preparation method of rosin-based acrylamide polymer
CN105348422B
A method for preparing UV-curable silicone-modified hyperbranched polyurethane material
CN111393608B
A photocurable solder paste and its preparation method
CN115401358B
Novel photo-curing soldering flux
CN103817460A
Photocuring soldering paste and preparation method thereof
CN115401358A